(untitled) (Philological Studies, 2024)
The ways in which armies and wars were depicted in literature depend on the period, the movement, the author, but also on the war in question and its significance for the community to which the author and the audience belong. The avant-garde is a literary and artistic phenomenon that borrows its name from military terminology, and the first manifesto of futurism announced a renewed singing about war, declaring it "the world’s only hygiene". After the emergence of futurism and the avant-garde, two world wars and one global "cold war" indeed marked the 20th century, and thus many artistic trends of that time, both in high and popular culture. Punk is not an exception either, and war will impose itself as one of the central themes in punk as well. This text is part of a wider research on punk as a possible avant-garde of European pop culture, thinking about the avant-garde in the terms set by Aleksandar Flaker and Edoardo Sanguineti. From such a perspective, the article offers an overview of a selected corpus of Yugoslav punk songs about armies or wars through several thematic groups, with the specifics by which these representations differ from those of their contemporary punk and post-punk songs about wars from NATO member countries, such as the UK and Italy. Considering the context of the research, a review is also given of how punk singing about war coincides with the procedures of some historical avant-gardes which also dealt with war themes, and special attention is given to the aspects of contestation and optimal projection according to Flaker and the impulse of anarchy according to Sanguinetti, with an awareness of the problems of political literature in general.